Further examination of video‐based preference assessments without contingent access. Issue 1 (20th September 2018) - Brodhead, Matthew T.; Kim, So Yeon; Rispoli, Mandy J.
Abstract : The first purpose of this study was to attempt to replicate previous findings that video‐based preference assessments without access to selected stimuli may accurately predict relative reinforcing efficacy of stimuli. To do this, we conducted a concurrent operant reinforcer assessment in which we evaluated the relative reinforcing value of highly preferred and less preferred items identified in a video‐based preference assessment. The second purpose of this study was to begin to evaluate the potential behavioral mechanisms responsible for the validity of this assessment. To conduct this analysis, we evaluated the relative reinforcing value of those same stimuli depicted in video format and then compared results to results obtained during the reinforcer assessment for tangible stimuli. For all five participants, stimuli identified as highly preferred functioned as reinforcers, and four of five participants, responding during the reinforcer assessment was similar in the presence of tangible stimuli and videos depicting those stimuli.